The Care of Environment in the Characters Pandawa of Mahabrata's Story: The Study of Literature Ecology - Ayu Indriani; Juanda; Agussalim AJ, Andi (Ethical Lingua: Journal of Language Teaching and Literature, 2023)
This writing examines a non-fiction prose by using the study of literary ecology. Literary ecology is a study related to the environment that arises from the results of thinking about ecological problems in literature. This writing aims to describe the Pandawa character's attention to the environment, the form of the Pandawa character's concern for the environment, and the interaction of the Pandawa character towards the environment in the Mahabharata story. The formulation of the problem in this writing is as follows, namely (1) How is the concern of the Pandawa character towards the environment depicted in the Mahabharata story?; (2) What is the form of the Pandawa character's concern for the environment described in the Mahabharata story?; and (3) How is the interaction between Pandawa figures and the environment described in the Mahabharata story? This type of research is a qualitative literature study model using an ecological literature approach. The main focus in this research is to describe the environmental care attitude of the pandawa character in the Mahabharata story. The data source is the text of the Mahabharata transliterated by C. Rajagopalacari. The data are in the form of words, phrases, dialogues, and sentences in the Mahabharata story which contain attention, forms of concern, and interactions of Pandawa characters towards the environment. Data collection using documentation techniques. Data analysis using interactive analysis techniques. The results of the discussion show the concern of the Pandawa characters for the environment, namely Nakula and Sadewa for livestock, there is a form of concern for the Pandawa characters for the environment, namely rebuilding the abandoned old city, and the interaction between Pandawa figures and nature, namely using rivers and snake venom as an antidote to poison in the story. the.